ENT 530 Social Media Portfolio: Viaggio Bag / Muhammad Izdihar Fadhli Ramly - Ramly, Muhammad Izdihar Fadhli (2021)
Viaggio Bag is an online business that is proposing a comfortable and wonderful experience to all traveller out there. We are using Facebook platform to promote and advertising our product to our target customer. A Facebook is very friendly user as it easy to use and equipped with many facilities to use as we can make a posting in the wall also through Facebook story. Nowadays, Facebook has been used worldwide, thus it increases our target customer as this platform is able to connect two people in any situation and wherever we are. Our main idea is we would like to enlighten society that investment for our good quality product is totally worth it. Especially to people who wants their travel to be more comfortable, our product is the answer for it. Our bag is being produce from only quality component part. So, our customer doesn’t have to worry about longevity of the bag. It also included with many features that will be helpful to our customer during travelling. Our target customer is all from family to one person to travel. It can be for woman or man. Our bag is suitable to use for everyone who love to travel. We also target toward family customer who have many children. As our bag design is comfortable for a big family.